The Passive Antihero in Alameddine’s 'I, the Divine' and 'an Unnecessary Woman' - Salma Kaouthar Letaief; Yousef Abu Amrieh (Anglo Saxonica, 2022)
This article focuses on the gradual transformation of the female protagonist into a passive antihero figure in Rabih Alameddine’s I, the Divine (2001) and An Unnecessary Woman (2013). It assesses the traumatic experiences of war and patriarchy that have triggered each transformation. The regression of the two protagonists, namely Sarah in I, the Divine and Aaliya in An Unnecessary Woman is thoroughly scrutinized in relation to the traumatic events of war and the oppressive patriarchal mores that these female protagonists encounter and experience. Sarah and Aaliya exhibit some typical features of a passive postmodern antihero such as acceptance, submission, lack of action, alienation, mechanistic dehumanization and estrangement. The absurdity of their lives is manifested in their acceptance of the absence of free will. All these features make of them prototypical passive, estranged and dehumanized antiheroes. The analysis of the female antiheroes in this research relies on the theoretical framework of feminist psychic trauma in order to relate the traumatic turmoil of the female characters to patriarchy and war following Laura Brown’s article “Not Outside the Range: One Feminist Perspective on Psychic Trauma” (1995). In other words, this article examines mainly the external factors that engendered the two protagonists’ transformation into passive antiheroes. The analysis endeavors to highlight that the protagonists follow the passive model, one of the prototypes of the antiheroic archetype.